BUILDING SYSTEM OF SAVING WATER FIRE EXTINGUISHER BASED ON MICROCONTROLER ARDUINO MEGA 2560 - Edi Kurniawan; Henna Nurdiansari; Renta Novaliana Siahaan; Diana Alia; Mochammad Zaqi Arif; Pradika Maestu Putra Ryan Wibowo (Jurnal Maritim Malahayati, 2023)
Fire hazards could be happened anywhere, it could be on a land (houses, buildings, forests, etc.) or on the sea (ships). This incident was occurred at KM Artamina Jaya. Fire prevention action performed by eliminate three elements of oxidation reaction, these are: fuel, oxygen, and heat. A method to break the three elements is spray water to the fire source. Existing or common fix fire distinguish usually use water spray or sprinkle. It takes a large amount of water to extinguish the fire and it conduce wets areas where not affected by fire. So that this research was invent to design a water-saving fire extinguish system based on Arduino Mega microcontroller. This study use 5-channel infrared flame sensors to detect the location of a fire and a DC motor sensor to spray water. By using 5-channel infrared flame sensors, the Arduino Mega microcontroller can determine which DC motor to spray water. The focus of this research is how to activate the fire extinguish pump or water sprayer according to the channel on the infrared flame sensor, which detects the source of the fire, and the system can activate more than one pump.